Hypomethylation of GCNT2 isoform A correlates with transcriptional expression and is associated with poor survival in acute myeloid leukemia - Wu, De-hong; Qiu, Hong-chun; Xu, Jing; Lin, Jiang; Qian, Jun (Frontiers in Immunology, 2025)
BackgroundThe function of GCNT2 has been documented to act as an oncogenic driver or tumor suppressor in different types of tumor, but the role of GCNT2 and the epigenetic regulation mechanism in AML, however, has not yet been clarified. This study aimed to assay the expression and methylation profile of GCNT2 in AML, and further elucidate the clinical significance.MethodsMultiple datasets from the Gene Expression Omnibus (GEO) and The Cancer Genome Atlas projects (TCGA) were used to explore the expression and methylation profile of GCNT2 in normal hematopoiesis and AML. A pan-cancer analysis was performed to define the survival implications of GCNT2 across multiple cancers including AML. The relationships between GCNT2 expression/methylation and clinicopathologic features were investigated using a TCGA-AML dataset. Correlation analysis was performed to explore the relationship between transcriptional expression and DNA methylation. Differentially expressed genes (DEGs) on the KEGG pathway and GO terms were visualized using DAVID. Gene Set Enrichment Analysis (GESA) was carried out to assess the underlying mechanism. The relationship between methylation and immune cell infiltration was also examined.ResultsGCNT2 expression was highest in hematopoietic stem cells (HSC) but gradually decreased during the hematopoiesis differentiation, the monocytes, however, remained a high level of GCNT2 as an exception. In AML, GCNT2 was down-regulated as compared to normal hematopoiesis but was much higher in contrast to normal peripheral blood samples. Data from a pan-cancer analysis revealed that high-expressed GCNT2 contributed to a worse OS for AML. DNA methylation of GCNT2 showed a distinctive co-methylation pattern in AML and significantly negatively correlated with transcriptional expression. Methylation in the transcriptional start site of isoform A plays a critical role in the epigenetic regulation of GCNT2 expression. The silence of GCNT2 in AML was attributed to DNA methylation. Hypomethylation of isoform A significantly predicted poor survival in AML, linking to several cytogenetic and molecular abnormalities, such as t (8:21), inv (16), t (15;17), and genes mutations of DNMT3A, CEBPA, RUNX1, and WT1. Enrichment analysis disclosed that hypomethylation of isoform A was involved in the immune system, and it was further revealed that hypomethylation of isoform A was tightly associated with immune cell infiltration and could be served as a promising indicator for immunotherapy.ConclusionsOur comprehensive research demonstrated that GCNT2 acted as an oncogene in AML, and was epigenetically regulated by DNA methylation in isoform A. Hypomethylation of isoform A could be served as a promising indicator to identify the high-risk AML patients who might be responsive to immunotherapy.